2021
DOI: 10.3390/jcm10173833
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Impacts of Exercise on Cardiovascular Remodeling

Abstract: Cardiovascular diseases (CVD) remain the leading cause of death in men and women. Biological sex plays a major role in cardiovascular physiology and pathological cardiovascular remodeling. Traditionally, pathological remodeling of cardiovascular system refers to the molecular, cellular, and morphological changes that result from insults, such as myocardial infarction or hypertension. Regular exercise training is known to induce physiological cardiovascular remodeling and beneficial functional adaptation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 197 publications
(323 reference statements)
1
8
0
1
Order By: Relevance
“…In addition, Rakobowchuk et al (2008) observed the FMD was significantly improved after 6 weeks of 65% VO 2peak (vigorous) intensity aerobic exercise, which was also consistent with our study. However, another study reported that both moderate-intensity and vigorous-intensity had a beneficial effect on improving vascular endothelial function (Islam et al, 2021). Therefore, further prospective and intervention studies were needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rakobowchuk et al (2008) observed the FMD was significantly improved after 6 weeks of 65% VO 2peak (vigorous) intensity aerobic exercise, which was also consistent with our study. However, another study reported that both moderate-intensity and vigorous-intensity had a beneficial effect on improving vascular endothelial function (Islam et al, 2021). Therefore, further prospective and intervention studies were needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is curious that we observed a lower TL CO in women with a PFO, but not in men with a PFO. This might be attribugtable to cardiopulmonary differences between men and women (i.e., smaller lungs and airways; Dominelli et al., 2018; Peters et al., 2021; Sheel et al., 2009) and heart sizes and pulmonary pressures in women (Islam et al., 2021), leading to differences in cardiac output, pulmonary pressures and pressure gradients across the right and left atrium during the TL CO breath‐hold manoeuvre. Ultimately, the combined effect(s) could be a greater blood flow across the PFO and a difference in TL CO in women with versus without a PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Data from trials on D hormone supplementation, either alone or combined, are unsatisfactory likely due to the high variability in protocols and heterogeneity of the studied populations, since general health status, ethnicity, sedentary habit are often not defined, as recently summarized elsewhere [ 80 , 81 ]. Furthermore, recent evidence highlights the major role of exercise-induced sex-dependent heart remodeling during life of men and women at different ages, either sedentary or physically active [ 129 ]. This topic is not addressed in the present review, both for length limits and because, in our opinion, it would deserve a dedicated issue.…”
Section: Discussionmentioning
confidence: 99%
“…The well-perfused oxygenation is one of the mechanisms underlying cardio-protection in healthy female heart. However, recent studies on exercise-induced remodeling in males and females show that female cardiac cells likely retain a lesser degree of metabolic flexibility to adaptation in stress or disease conditions [ 129 ]. Noticeably, in cardiac cells vitamin D is reported to impinge on the energy substrate balance, regulating fat uptake/fatty acid β-oxidation via sirtuin 3 [ 75 ].…”
Section: Vitamin D and Cardiomyocyte Remodelingmentioning
confidence: 99%